« Danser la relation » - Marie Mazzella di Bosco (Ateliers d'Anthropologie)
“Connecting with oneself, with others, and with the world”: this is a common description of the ambition of “free-form mindful dances” such as the 5 Rhythms Dance). Though neglected by scientific and artistic communities, these practices can nevertheless be viewed as relational experimentation laboratories that bring into play something that goes beyond both danced movement and a mere process of wellbeing. In them, dance is a tool for constructing special relational modes: through the body in motion, subtle interpersonal negotiations are at play, underlying broader relational issues that prove to be fundamental if one pays attention to the accounts and actions of the dancers. In a brief ethnography of the gestures, postures and sensory perceptions at work, this article analyses how danced interactions are induced, begun, developed and interpreted, thus shedding light on the nature of these relational modes proper to dance.